The San Joaquin kit fox : biology, ecology, and conservation of an endangered species - Cypher, Brian L. (Comstock Publishing Associates, an imprint of Cornell University Press, 2024)
""This book provides a summary and synthesis of the information currently available on the San Joaquin kit fox, a species that has been on the US endangered species list since 1967"--Provided by publisher"-- Provided by publisher.
Keywords: San Joaquin kit fox.; San Joaquin kit fox -- Ecology.; San Joaquin kit fox -- Conservation.; Vulpes velox mutica.; Vulpes velox mutica -- Écologie.; Vulpes velox mutica -- Conservation.; SCIENCE / Life Sciences / Biology.; Electronic books.